Impact of serum vitamin D level on severity of asthma in children - Sachdeva, Payasvi Baweja; Dutta, Jusmita; Joshi, Sheloj; Anand, Shweta (International Journal of Research in Medical Sciences, 2021)
Background: Asthma is the most common chronic respiratory disease among children characterized by reversible airway obstruction. Vitamin D plays an important role in many immune and allergic diseases and it may have a role in asthmatic patients, however this association yet remains uncertain. The present study was designed to assess the level of serum Vitamin D in patients with bronchial asthma and it’s correlation with disease severity. Methods: A prospective observational study was performed from April 2019 to February 2020 in the Paediatric OPD of LNMC and JK Hospital Bhopal. All 90 children with physician diagnosed bronchial asthma (mild, moderate and severe) aged 10 to 18 years of both genders who have come in the OPD (total enumeration sampling) during the above mentioned period were enrolled in to the study. The patients were grouped on the basis of Vitamin D sufficiency and Vitamin D levels were correlated with disease severity. Results: The study comprised 54 boys (60%) and 36 girls (40%) with mean age of 15.1±3.96. Out of 90 children enrolled, 46 had good control over asthma and 37 had uncontrolled asthma. As regards asthma control, 25-OH Vitamin D was lowest among patients with uncontrolled asthma. Conclusions: Vitamin D deficiency was highly prevalent in asthmatic patients and there was a direct and a significant relationship between serum Vitamin D levels, severity of asthma, control of asthma, serum IgE levels and blood eosinophils count. Thus, measuring serum levels of Vitamin D followed by supplementation could be considered in the routine assessment of patients with bronchial asthma.